SDN Elastic Optical Network-based Intelligent Service Orchestration for Power Communication Network - KANG Zhongmiao; WU Zanhong; ZHANG Peiming; HUANG Donghai; BAO Yuben; LU Wenbing; ZHANG Sunxuan (Journal of Harbin University of Science and Technology, 2024)
Aiming at the differentiated service orchestration for power communication network, this paper firstly constructs a power communication network architecture based on SDN elastic optical network and completes the data exchange between the service layer and the SDN control layer to support the normal operation of a variety of power communication network services with different priorities in the distribution network. Secondly, an adaptive service priority-aware learning-based service orchestration algorithm for power communication network is proposed, which adaptively adjusts the exploration factor according to different service priorities and balances the exploration and exploitation of different priority service arm selections, thereby ensuring the high transmission of high-priority service and reducing the network cost. Finally, the performance advantages of the proposed algorithm in terms of energy efficiency and delay are verified by numerical analysis. The research content of this paper can provide a reference for the low-latency and efficient transmission of differentiated service data flow of power communication network, thereby supporting the efficient operation of power communication network.